FINANCIAL INCLUSION AND MUQASAH AR-RIBHI IN REPAYMENT FINANCING IN BMT - DISFA LIDIAN HANDAYANI; JULITASARI JULITASARI; CITRA LESTARI; CITRA PERTIWI; DIAN PERTIWI (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2021)
Baitul Maal wat Tamwil (BMT), as a representation of an inclusive financial institution, must have a special strategy to attract and expand access to people who need financing. The portion of Murabaha financing is the largest attracting customer interest from the total financing at Islamic financial institutions in Indonesia, including BMT, compared to other contracts. Therefore, implementing a policy on Murabaha financing at BMT basically supports financial inclusion. One of the strategies implemented by BMT is to provide a Margin discount (Muqasah Ar-Ribhi) in Repayment Before due date on Murabaha financing at one of the BMTs in South Sumatra, namely BMT Assyafi'yah Berkah Nasional, Tugumulyo Ogan Komering Ilir Branch, South Sumatra. The research data was obtained through a qualitative study process sourced from BMT. Primary data related to the application of the Muqasah Ar-Ribhi Application in Repayment Before due date in Murabaha Financing at BMT As-Syafi'iyah, was obtained through interviews with both management and customers, and supported by several archives and documents from BMT. Secondary data is sourced from books, journals, and records related to Margin deductions (Muqasah Ar-Ribhi) or inclusion of financial institutions. This research begins with a desk review of secondary data and materials from previous studies, then continues with observations, interviews, and case studies. Research data were analyzed following three stages of Huberman's analysis: data reduction, data display, and data verification. The results of the study indicate that BMT As-Syafi'iyah applies a policy of giving margin discounts, whose accounting application is in accordance with PSAK 102, where the profit of Murabaha is recognized proportionally. Regarding the amount of the margin discount given to the buyer, it is left to BMT's policies and considerations. The research findings also show that the existence of this policy has accelerated the expansion of access for other customers who need financing, so that it can be said to support the inclusion of financial institutions.